The Meaning of Welcoming Dance in Ijab Qabul Procession in Talang Bunut Village, Amen Sub-District Lebong Regency Bengkulu Provision - Aninda Nissafitri; Darmawati (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
The purpose of this study is to describe the Meaning of Welcoming Dance at the Ijab Qabul Procession in Talang Bunut Village, Amen District, Lebong Regency, Bengkulu Province. This type of research is qualitative research with descriptive methods. The researcher's own research instruments and assisted by supporting instruments in the form of writing, cameras or mobile phones, and flash drives. Data collection techniques are carried out through literature studies, observations, interviews, and documentation. The steps in analyzing data include data reduction, data presentation, and conclusions. The results revealed that the Welcoming dance in the ijab qabul procession has the meaning of maintaining the security of the bride and the location of the event from all forms of unwanted disturbances. Textually, the meaning of the Welcome Dance, namely: (1) Preparation movements as a form of readiness to welcome guests. (2) The motion of starting to dance shows the dancer starting to greet guests. (3) The motion of presenting betel as a symbol of the custom of welcoming guests. (4) The gesture of giving a shawl means that the groom has been well received by the bride's family. (5) The motion to pave the way means that the bride's family has received the groom's goodwill. (6) Return to position means ensuring the event location is safe. (7) The gesture of sitting as a salute to welcome guests. (8) The gesture of giving way means giving way to the groom to carry out his good intentions. (9) Jang Pat Petulai silat movement means ensuring the security of the event location. (10) Sowing motion.